Geochemistry of Major, Trace, and Rare Earth Elements in Biglar Permo-Triassic Bauxite Deposit, Northwest of Abgarm, Ghazvin Province, Iran - A.A Calagari (Journal of Sciences, Islamic Republic of Iran)
Biglar Permo-Triassic bauxite deposit is located in ~15 km northwest of Abgarm, southwest of Ghazvin province, west of central Iran. It consists of 8 stratiform and discontinuous bauxite lenses lying along the contact of Ruteh (Permian) and Elika (Triassic) carbonate formations. Petrographically, the bauxite ores exhibit collomorphic-fluidal, pseudo-breccia, pseudo-porphyritic, panidio-morphic-granular, nodular, and skeletal textures indicative of authigenic origin. Weathering of andesitic parent rocks led to the formation of Ferruginous laterite, bauxitic clay, and siliceous bauxite. Mass change calculations of elements indicate that Si, and Ba were depleted during bauxitization and Al, Ti, Zr, Nb, Hf, Ga, U, Th, V, and Cr were enriched. However, Fe, Y, Rb, Sr, Co, Ni, LREEs, and HREEs experienced leaching-fixation mechanism during the development of the residual system. Based upon obtained data, the available organic matters, pH variations in weathering solutions, adsorption process, functioning of carbonate bedrock as a geochemical barrier, existing in resistant minerals, and fixation in the neomorphic phases have been shown to play significant role in distribution of trace and rare earth elements. Further geochemical considerations indicate that minerals such as monazite, rhabdophane, belovite, churchite, and xenotime are the potential hosts for rare earth elements in Biglar bauxite deposit.